Preparation and Characterization of Catalyst Zn/Al2O3 Catalyst using Dry and Wet Impregnation Method - Selpiana Selpiana; David Bahrin; Muhammad Ridho Habibie; Faras Saskia Samara (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
Metal supported catalysts are used in many catalytic cracking processes. Experiments have shown that the increasing of metal loaded within the catalyst support may affected the increasing of cracking process conversion and selectivity. Therefore, a fundamental understanding of increasing the metal loaded is needed. In this study, Zinc on Alumina supported catalyst was prepared using the dry and wet impregnation methods to obtain the best amount of Zn metal content in Al2O3 as catalyst support with good characteristics for catalytic cracking. The prepared precursor solution in wet impregnation method was varied in concentration. While the dry impregnation method was varied in drying temperature. The Atomic Absorption Spectroscopy test results the metal content of Zn on the variation of precursor solution concentration on 0,5 M; 2,5 M; 4,5 M  are 1,06%; 9,65%; 15,91% and in the variation of the drying temperature at 25ºC, 50ºC, and 80ºC respectively are 18,32%; 12,48%; and 39,07%. Characteristics analysis through X-Ray Diffraction, Brunauer-Emmet-Teller, and Scanning Electron Microscopy tests have also been carried out on samples with the highest metal content of 39,07% and samples with the lowest metal content of 1,06%.